ANALISIS BEBAN KERJA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN SUMEDANG - Andi Gusti (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2020)
This study aims to explain the workload of employees at the One Stop Integrated Investment and Service Office (DPMPTSP) of Sumedang Regency. This study uses a descriptive design with a quantitative approach through descriptive statistics techniques. It was found that the job descriptions were distributed evenly to the employees in the office environment. The general structural and functional position holders have performed their job duties quite well. On average, the workload of employees has a unit efficiency level of 1.17. That is, on average they carry out work 17% exceeding the ideal workload. Thus, the need for employees in the office is 59 employees. Keywords: Workload Employee Performance; Human Resources Management